Real Time Monitoring, Visualization And Prediction Of Coal Mine Monitoring System Based On Linear Regression Algorithm And Labview - Kanaga Durga Deenadayalan, S Jayanthy, A Arunraja (International Journal of Advanced Science and Technology, 2020)
The paper proposes an embedded system to monitor the parameters for the safety of miners working in the coal mines. The parameters measured are temperature, humidity and CO2 level. The measured data are then applied to the Linear Regression algorithm implemented in the STM32F401RE nucleo board – ARM cortex M4. If the measured data exceed the threshold, then an alarm is turned ON in the mine. The measured parameters are then sent to the base station wirelessly using Zigbee module. The parameter values along with the predicted outcomes are visualized using LabVIEW installed in a computer at the base station in a graphical format. The LED’s in the VI will glow RED if the measured data exceed the threshold. The experimental results indicate that the system predicts the conditions in the mine accurately.